IGF2BP2 Regulates MALAT1 by Serving as an N6-Methyladenosine Reader to Promote NSCLC Proliferation - Han, Le; Lei, Guangyan; Chen, Zhenghong; Zhang, Yili; Huang, Chen; Chen, Wenjuan (Frontiers in Molecular Biosciences, 2022)
Insulin-like growth factor 2 (IGF2) mRNA-binding protein 2 (IGF2BP2) is an important posttranscriptional regulatory for stability and m6A modification. Here we investigated the role of IGF2BP2 in non-small cell lung cancer (NSCLC) proliferation. TCGA database was used to predict the expression and clinical significance of IGF2BP2 in normal and NSCLC samples. The expression of IGF2BP2 was further validated in NSCLC samples from surgery. Then we performed the functional study in NSCLC cell lines through overexpressing and knocking down IGF2BP2 in NSCLC cell lines in vitro and in vivo. The mechanism of interaction between IGF2BP2 and lncRNA metastasis associated lung adenocarcinoma transcript 1 (MALAT1) in NSCLC proliferation was determined by RIP assay. We demonstrated that IGF2BP2 is highly expressed in NSCLC, and positively associated with poor overall survival (OS) and disease-free survival (DFS). We identified that lncRNA MALAT1 is a target of IGF2BP2 in NSCLC. IGF2BP2 promotes MALAT1 stability in an m6A-dependent mechanism, thus promoting its downstream target autophagy-related (ATG)12 expression and NSCLC proliferation.